Educational Application of Satera Jontal and Sumbawa Culture Based on Augmented Reality to Realize Indonesia SDGs 2030 - Wahyu Prama Pratama Hpar; Wawan Kurniawan; Muhammad Rendi Maulana; Muh.Rizky Destiawansyah; Herliana Rosika; Tomáš Jeřábek (English and Tourism Studies, 2025)
Indonesia is recorded as an archipelagic country with cultural diversity. However, technological advancement and globalization have an impact on local culture. One of them is that Sumbawa's culture is threatened to be eroded and forgotten due to the younger generation shifting towards Western culture or K-pop. Everyone on the island of Sumbawa, especially students, is expected to know and enhance their love for the local culture of Sumbawa. Based on this, this research aims to examine the concept of SAJODAR as an educational application of Satera Jontal and Sumbawa regional culture based on Augmented Reality (AR) to enhance students' knowledge and love for Sumbawa's local culture. The method used in this research is the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to construct a learning system. The ADDIE development model is more effective, rational, and comprehensive for developing a product. The analysis results show a relatively high attention rate in the realm of technology-based cultural learning, to facilitate students, especially in using the SAJODAR application as a medium to enhance the love for Sumbawa culture.